The role of echinacoside-based cross-linker nanoparticles in the treatment of osteoporosis - Dandan Hu; Chunan Cheng; Zhen Bian; Yubo Xu (PeerJ, 2024)
Background Current drugs for treating osteoporosis may lead to toxic side effects. Echinacoside (ECH) is a natural small molecule drug. This study examined and compared the therapeutic effects of cross-linker (CL)-ECH and ECH-free nanoparticles on osteoporosis. Methods Echinocandin-based CL-ECH nanoparticles were prepared, and the nanoparticle size and drug loading were optimized and characterized by adjusting the ratio. The antioxidant effect of CL-ECH nanoparticles on bone marrow-derived macrophages (BMDMs) was analyzed using flow cytometry, immunofluorescence staining and quantitative real-time polymerase chain reaction (qRT-PCR). Bone marrow stromal cells (BMSCs)-based detection of bone-producing effects was conducted using alkaline phosphatase (ALP), Alizarin Red S (ARS) and qRT-PCR. TRAP, phalloidin staining, and qRT-PCR was performed to detect osteogenesis-inhibiting effect on BMDMs. CL-ECH nanoparticles were applied to treat an ovariectomized (OVX) mouse model at low doses. Results Compared to ECH, CL-ECH nanoparticles suppressed oxidative stress in BMDMs by promoting NRF-2 nuclear translocation, which inhibited the production of both reactive oxygen species (ROS) and osteoclast production through downregulating NF-κB expression, with limited effect on the osteogenesis of BMSCs. In vivo studies showed that low-dose CL-ECH nanoparticles markedly improved bone trabecular loss compared to ECH administration in the treatment of osteoporosis. Conclusions The current discoveries provided a solid theoretical foundation for the development of a new generation of anti-bone resorption drugs and antiosteoporosis drugs.